Green supply chain management (gscm) performance implemented by the textile industry of Gazipur District, Dhaka - Syed Shakil Ahmed; Tauhima Akter; Yuchao Ma (Logistics, 2018)
Globally, pollution has spurred corporate players to use eco-friendly polishes and the textile industry is not an uncommon case. Textile commercial enterprises should adopt the same green supply chain management (GSCM) practices and this research paper seeks to identify the green supply chain management (GSCM) practices embraced by a textile industry in Gazipur District, Dhaka. Essential information was sourced from 200 respondents to support the review. Information was dissected with the assistance of weighted arithmetic mean and chi-square tests and it has been concluded that a huge number of green supply chain management practices are being embraced by the textile industries of Gazipur district.
Keywords: 650; green supply chain management; ISO 14001; textile industry